2002
DOI: 10.1001/jama.287.18.2414
|View full text |Cite
|
Sign up to set email alerts
|

The Glycemic Index

Abstract: The glycemic index was proposed in 1981 as an alternative system for classifying carbohydrate-containing food. Since then, several hundred scientific articles and numerous popular diet books have been published on the topic. However, the clinical significance of the glycemic index remains the subject of debate. The purpose of this review is to examine the physiological effects of the glycemic index and the relevance of these effects in preventing and treating obesity, diabetes, and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
380
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,512 publications
(394 citation statements)
references
References 101 publications
8
380
1
5
Order By: Relevance
“…High-amylose starches can also be processed as a source of RS with or without further modification, which has nutritional benefits as outlined previously [98,213]. It reduces postprandial glycemic and insulin responses, thus reducing the risk for developing type II diabetes, obesity, and cardiovascular diseases [115,123]. The fermentation of RS by gut microflora can produce short-chain fatty acids, especially butyrate, which can prevent the incidence of colon cancer [185].…”
Section: Starch Biosynthesis-structure-properties Relationshipsmentioning
confidence: 99%
“…High-amylose starches can also be processed as a source of RS with or without further modification, which has nutritional benefits as outlined previously [98,213]. It reduces postprandial glycemic and insulin responses, thus reducing the risk for developing type II diabetes, obesity, and cardiovascular diseases [115,123]. The fermentation of RS by gut microflora can produce short-chain fatty acids, especially butyrate, which can prevent the incidence of colon cancer [185].…”
Section: Starch Biosynthesis-structure-properties Relationshipsmentioning
confidence: 99%
“…5 Although no long-term clinical trials have examined the effects of dietary GI on body weight regulation, single-day studies have shown lower satiety, increased hunger, or higher voluntary food intake after consumption of high-GI compared with low-GI meals. 1 Two medium-term studies of 5 and 12 weeks also showed improved weight or fat loss on low-GI diets. 6,7 A pioneering study by Ludwig et al 8 showed that obese children who were given high-, medium-, or low-GI breakfasts and lunches of equal-energy content had a voluntary food intake for the rest of the day that was 53% higher after the high-GI breakfast.…”
mentioning
confidence: 97%
“…[1][2][3][4] It has been hypothesized that low-GI foods may benefit weight regulation in 2 ways: by promoting satiety and promoting fat oxidation at the expense of carbohydrate oxidation. 5 Although no long-term clinical trials have examined the effects of dietary GI on body weight regulation, single-day studies have shown lower satiety, increased hunger, or higher voluntary food intake after consumption of high-GI compared with low-GI meals.…”
mentioning
confidence: 99%
“…It consists of ␣-glucan polymers with ␣1¡4 linkages and a low percentage of ␣1¡6 linkages, in the form of amylose and branched amylopectin (2). Starches are applied in various industrial products such as food, paper, and textiles, often after processing by physical, chemical, or enzymatic treatment (3-6).Dietary fibers and low-glycemic-index (low-GI) food are considered healthy food contributing to our long-term well-being (7,8). Of all the nutritional types of starch, slowly digestible starch with low GI has drawn the strongest interest.…”
mentioning
confidence: 99%
“…Dietary fibers and low-glycemic-index (low-GI) food are considered healthy food contributing to our long-term well-being (7,8). Of all the nutritional types of starch, slowly digestible starch with low GI has drawn the strongest interest.…”
mentioning
confidence: 99%